Holocene History of Río Tranquilo Glacier, Monte San Lorenzo (47°S), Central Patagonia - Sagredo, Esteban A.; Reynhout, Scott A.; Kaplan, Michael R.; Aravena, Juan C.; Araya, Paola S.; Luckman, Brian H.; Schwartz, Roseanne; Schaefer, Joerg M. (Frontiers in Earth Science, 2021)
The causes underlying Holocene glacier fluctuations remain elusive, despite decades of research efforts. Cosmogenic nuclide dating has allowed systematic study and thus improved knowledge of glacier-climate dynamics during this time frame, in part by filling in geographical gaps in both hemispheres. Here we present a new comprehensive Holocene moraine chronology from Mt. San Lorenzo (47°S) in central Patagonia, Southern Hemisphere. Twenty-four new 10Be ages, together with three published ages, indicate that the Río Tranquilo glacier approached its Holocene maximum position sometime, or possibly on multiple occasions, between 9860 ± 180 and 6730 ± 130 yr. This event(s) was followed by a sequence of slightly smaller advances at 5750 ± 220, 4290 ± 100 (?), 3490 ± 140, 1440 ± 60, between 670 ± 20 and 430 ± 20, and at 390 ± 10 yr ago. The Tranquilo record documents centennial to millennial-scale glacier advances throughout the Holocene, and is consistent with recent glacier chronologies from central and southern Patagonia. This pattern correlates well with that of multiple moraine-building events with slightly decreasing net extent, as is observed at other sites in the Southern Hemisphere (i.e., Patagonia, New Zealand and Antarctic Peninsula) throughout the early, middle and late Holocene. This is in stark contrast to the typical Holocene mountain glacier pattern in the Northern Hemisphere, as documented in the European Alps, Scandinavia and Canada, where small glaciers in the early-to-mid Holocene gave way to more-extensive glacier advances during the late Holocene, culminating in the Little Ice Age expansion. We posit that this past asymmetry between the Southern and Northern hemisphere glacier patterns is due to natural forcing that has been recently overwhelmed by anthropogenic greenhouse gas driven warming, which is causing interhemispherically synchronized glacier retreat unprecedented during the Holocene.